2020
DOI: 10.1093/tas/txaa078
|View full text |Cite
|
Sign up to set email alerts
|

Broccoli byproduct-wheat straw silage as a feed resource for fattening lambs1

Abstract: The effect of feeding broccoli byproduct-wheat straw silage (BBWS) (69:31 ratio, DM basis) on performance, microbial N synthesis (MNS), rumen and blood parameters in Fashandy lambs were evaluated. Three diets, with equal metabolisable energy and crude protein (CP) with a forage to concentrate ratio of 27:73 (DM basis), were formulated in which forage (lucerne and wheat straw) was replaced by BBWS (0, 100, or 200 g/kg of diet DM). These were assigned to 3 groups (n = 15/group) in a completely randomized block d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 27 publications
1
11
0
Order By: Relevance
“…pekinensis) or control that free from any leaves and they showed a significantly (P < 0.05) higher of feed intake and body weight gain (529 g DM/day and 87.5 g/day, respectively) for cauliflower group and significantly lower of feed intakes of cabbage and Chinese cabbage groups comparing with those of control ration. On the other hand, Partovi et al (2020) documented that fattening lambs fed on BB-wheat straw silage in substituting up to 200 g of forage had no effect on DMI values between the tested groups and the control one. Also, Hu et al (2011) claimed that productive performance did not affected by inclusion of broccoli leaf and stem powder in laying hens diets at 0, 30, 60 and 90 g/kg of the diets.…”
Section: Milk Production and Its Macro-compositionmentioning
confidence: 93%
See 4 more Smart Citations
“…pekinensis) or control that free from any leaves and they showed a significantly (P < 0.05) higher of feed intake and body weight gain (529 g DM/day and 87.5 g/day, respectively) for cauliflower group and significantly lower of feed intakes of cabbage and Chinese cabbage groups comparing with those of control ration. On the other hand, Partovi et al (2020) documented that fattening lambs fed on BB-wheat straw silage in substituting up to 200 g of forage had no effect on DMI values between the tested groups and the control one. Also, Hu et al (2011) claimed that productive performance did not affected by inclusion of broccoli leaf and stem powder in laying hens diets at 0, 30, 60 and 90 g/kg of the diets.…”
Section: Milk Production and Its Macro-compositionmentioning
confidence: 93%
“…Also, de Evan et al ( 2020) demonstrated that rumen CP degradability of broccoli stems was 9.8% higher (P<0.001) than that of florets and in contrary, in vitro intestinal DM and CP digestibility of stems was lesser than those of florets. On the other hand, Partovi et al (2020) demonstrated that fattening lambs fed a mixture of BB with wheat straw silage substituted up to 200 g of forage had no effect on the apparent digestibility of DM, EE, OM and CP. Contrary, Nkosi et al (2016) mentioned that the digestibility of OM and NDF were decreased with increasing the levels of discards cabbage (Brassica oleracea) incorporation into lambs diets (73 % vs. 65 %; 56 % vs. 47%, respectively; compared with those fed the control ration that free from discarded cabbage.…”
Section: Digestion Coefficients and Feeding Valuesmentioning
confidence: 95%
See 3 more Smart Citations